Photodynamic Therapy for Pododermatitis in Penguins - Sellera, Fabio Parra; Sabino, Caetano Padial; Ribeiro, Martha Simoes; Fernandes, Lorie Tukamoto; Pogliani, Fabio Celidonio; Teixeira, Carlos Roberto [UNESP]; Pereira Dutra, Gustavo Henrique; Nascimento, Cristiane Lassalvia (Wiley-Blackwell, 2014)
Pododermatitis is currently one of most frequent and important clinical complications in seabirds kept in captivity or in rehabilitation centers. In this study, five Magellanic penguins with previous pododermatitis lesions on their footpad were treated with photodynamic therapy (PDT). All PDT treated lesions successfully regressed and no recurrence was observed during the 6-month follow-up period. PDT seems to be an inexpensive and effective alternative treatment for pododermatitis in Magellanic penguins encouraging further research on this topic. (C) 2014 Wiley Periodicals, Inc.
Keywords: laser; photodynamic inactivation; photoinactivation; Spheniscus magellanicus; bumblefoot; phototherapy; methylene blue; light; antimicrobial; wound healing